2015
DOI: 10.14198/jhse.2015.101.11
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a physical education plan on psychomotor development profiles of preschool children

Abstract: Teixeira Costa, H.J., Abelairas-Gomez, C., Arufe-Giráldez, V., Pazos Couto, J.M., & Barcala-Furelos, R. (2015). Influence of a physical education plan on psychomotor development profiles of preschool children. J. Hum. Sport Exerc.,10(1),. This study aimed to investigate the influence of structured physical education on the psychomotor development of 3 to 5 year-old preschool children. The sample consisted of 324 students of both sexes (3 to 5 year-old) from 9 public kindergarten classes in Porto, Portugal. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 49 publications
3
33
0
7
Order By: Relevance
“…Among the four RCTs, significant increases in motor development were observed in the intervention groups (planned passive cycling or structured/organized physical activity) compared to the control groups (standard care) in three studies [ 90 – 92 ]. One intervention involved an infant sample [ 91 ]. In the fourth study, no significant differences in motor development were observed between the intervention (parents received physical activity recommendations from a nurse when their child was an infant) and control (no recommendations) groups [ 40 ]; however, physical activity was not significantly different between groups [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the four RCTs, significant increases in motor development were observed in the intervention groups (planned passive cycling or structured/organized physical activity) compared to the control groups (standard care) in three studies [ 90 – 92 ]. One intervention involved an infant sample [ 91 ]. In the fourth study, no significant differences in motor development were observed between the intervention (parents received physical activity recommendations from a nurse when their child was an infant) and control (no recommendations) groups [ 40 ]; however, physical activity was not significantly different between groups [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…This model reminds us that we must consider individual factors, environmental factors, and task factors understand motor development. The progressive acquisition of skills concerns both mental and motor activities are defined as psychomotor development (José et al, 2015). Infant psychomotor development seeks to provide children with several necessary skills to ensure good school performance (Fisher et al, 2005).…”
Section: Gross and Fine Motor Skills Developmentmentioning
confidence: 99%
“…Costa H.J. and others [12] presented the impact of structured programs and physical education classes with pre-school children on physical fitness indicators.…”
Section: Introductionmentioning
confidence: 99%